Evaluating surgical excision to prevent progression of oral precancerous lesions: Highlighting randomized controlled trials and cohort studies - Shanxin Zhou; Xinyu Zhang; Wei Liu; Weishi Chen (Elsevier, 2023)
Currently, surgical excision remains a common intervention for oral precancerous lesions (OPL). However, the studies focusing on conventional surgery by scalpel for OPL are not analyzed collectively in detail. Therefore, the objective of this short communication is to summarize and evaluate the evidence on scalpel surgery in preventing the progression of OPL patients. There are 16 eligible studies on surgery management of the recurrence (13 studies) or malignant transformation (13 studies) of OPL. The pooled recurrence rate (95% confidence interval) of OPL patients received scalpel surgery and laser therapy is 29.5% (26.3-33.0%) and 32.2% (26.1-38.9%), respectively. The pooled rate of malignant transformation of OPL patients received scalpel surgery, laser therapy, and clinical observation is 8.9% (7.3-10.9%), 6.0% (3.5-10.1%), and 10.2% (8.6-12.1%), respectively. The important limitation of current evidence available for prognosis of dysplastic OPL is based on retrospective observational studies. It highlights that surgical management of OPL needs more randomized controlled trials and cohort studies to explore more reliable methods for routine clinical use to facilitate high- or low-risk stratification and further select more appropriate treatment option.